2014
DOI: 10.1590/rou.2014.053
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of root canal cleaning, main and laterals, using different methods of final irrigation

Abstract: ResumoObjetivo: O objetivo deste estudo foi avaliar a eficácia da irrigação ultrassônica passiva (IUP), utilizando os fluxos intermitente ou contínuo, e da irrigação manual convencional (IMC) na limpeza de canais radiculares, principal e laterais simulados. Material e método: Os canais radiculares de 24 dentes artificiais foram preparados e os canais laterais foram confeccionados nos terços médio e apical. Os espécimes foram divididos em três grupos: G1-IMC, G2-IUP 1 (fluxo intermitente) e G3-IUP 2 (fluxo cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
7
0
3
Order By: Relevance
“…The simulated lateral canals were made in resin teeth, as already described, [22][23][24] with 0.20 mm of diameter, according to other studies which used resin blocks artificial teeth and natural teeth. 5,22,25 The radiological contrast solution was thickened with propylene glycol and bismuth oxide to provide consistency and radiopacity, 22,26 allowing radiographic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The simulated lateral canals were made in resin teeth, as already described, [22][23][24] with 0.20 mm of diameter, according to other studies which used resin blocks artificial teeth and natural teeth. 5,22,25 The radiological contrast solution was thickened with propylene glycol and bismuth oxide to provide consistency and radiopacity, 22,26 allowing radiographic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of softwares and tools to evaluate different irrigation protocols have already been used in previous studies. 22,26,28,30,31 The root canal cleaning using various irrigation methods in comparison to manual irrigation has been studied. Howard et al 32 observed a similar cleaning capacity, at 2 and 4 mm from WL, for three irrigation techniques, such as EndoVac, PiezoFlow and irrigation with needle (Max-i-Probe).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations